Eculizumab application during pregnancy in a patient with paroxysmal nocturnal hemoglobinuria: A case report with review of the literature - Lauritsch‐Hernandez, Lisa Sophie (Clin Case Rep, 2018)
Eculizumab is highly effective in inhibiting complement activation and has successfully shown to prevent complications and to improve quality of life in patients with paroxysmal nocturnal hemoglobinuria (PNH). Its application during pregnancy showed favorable fetal and maternal outcome in the presented case and has proven to be effective without raising safety concerns.